Diversity-oriented synthesis of spiroannulated benzofuran-3-one scaffold of leptosphaerin C and congeners via aryne insertion - Dhokale, Ranjeet A.; Mhaske, Santosh B. (Journal of Organic Chemistry, 2017)
A concise synthesis of functionalized cyclohexenone-fused spirobenzofuran-3-ones under mild reaction conditions was developed. The reaction proceeds via insertion of aryne into the C-O bond followed by a regioselective intramolecular conjugate addition. The use of silyl-protected acid was crucial for the transformation. This protocol was successfully applied for the synthesis of leptosphaerin C core and its novel analogues.